Pengaktifan Pengelolaan Sampah Melalui Kegiatan KKN Tematik di desa Kapuan kecamatan Cepu kabupaten Blora - Riska Andi Fitriono; Oktafian Suryo Wibawanto; Hairur Rozak; Fadya Intan Rahmawati; Anggi Sukma Indah; Avilia Zanata Astika Baktiar; Rosalia Imroatul Mufidah; Syahwa Agustin Rahmawati; Elen Anjelina; Salsabilla Haura Aghisny; Trianawati Ayuningtyas (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Community service activities through the real work study program with the theme of community service to overcome the problems of inorganic and organic waste in the Kapuan village community, Cepu district, Blora sub-district. this activity runs for 45 days reviewing the amount of inorganic and organic waste increases continuously so that it is used to reactivate the waste bank and organic waste as fish and poultry feed which is carried out in stages from determining the location, reviewing the location of activities, planning work programs, realizing work programs, and evaluating work. The results of community service activities through the KKN program have helped reduce inorganic and organic littering that generates money from the sale of waste.